The Influence of the Service Process on Service Quality: A Study of BPJS PROLANIS Patients at Prodia Clinic Jambi - Adam Permana Yudha; Boni Saputra (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2026)
The quality of healthcare services is a key indicator of the success of the National Health Insurance (JKN) system; however, the expansion of BPJS Kesehatan enrollment has not been fully accompanied by equitable service quality, as reflected by the gap in perceptions at the Prodia Clinic in Jambi, where 47% of PROLANIS patients rated the empathy aspect of service as only